1990
DOI: 10.2307/3759900
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Culture Conditions on Mycelial Growth and Luminescence in Panellus stypticus

Abstract: A pure culture ofPanellus stypticus was isolated from a mature basidiocarp and studied for its growth and luminescence abilities under various environmental and nutritional conditions. The culture was non-luminous growing submerged in defined liquid media with or without agitation. After a two-to three-day lag period on solid substrata, luminescence increased exponentially with a doubling time of 4 hours while the increase in colony radial growth was linear. On solid substrata, growth and total light emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 13 publications
1
20
1
2
Order By: Relevance
“…Maximum light emission occurred at the pe riphery of the culture when grown under normal laboratory light conditions. Similar results were reported by Bermudes et al (1990) for Panellus stypticus. Comparison of the light emission levels of some bioluminescent cultures is presented in Fro.…”
supporting
confidence: 80%
“…Maximum light emission occurred at the pe riphery of the culture when grown under normal laboratory light conditions. Similar results were reported by Bermudes et al (1990) for Panellus stypticus. Comparison of the light emission levels of some bioluminescent cultures is presented in Fro.…”
supporting
confidence: 80%
“…Airth et al [10] found an optimum temperature of 26³C for luminescence of A. mellea, while Risbeth [11] found that 25³C was the optimum temperature for growth of A. mellea on malt agar. Bermudes et al [4] and Berliner [6] reported the optimum temperature for luminescence of P. stipticus at 22³C and 18^26³C, respectively. Other studies have also found an optimum temperature for growth of basidiomycetes (wood-rotting) between 20 and 30³C [12,13].…”
Section: Temperature Experimentsmentioning
confidence: 99%
“…It has previously been noted that temperature a¡ects mycelial growth and luminescence of naturally biolumines-cent fungi [4,6,9,10]. Buller [9] found an optimum temperature between 10 and 25³C and a maximum temperature of 35^37³C for luminescence of P. stipticus.…”
Section: Temperature Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical studies of luminous fungi reported for the past 30 years include: the isolation of fluorescent compounds, i.e. ergosta-4,6,8 ( 14),22-en-3-one and a flavin, which showed a fluorescence emission spectrum identical to the bioluminescence spectrum (4)(5)(6); the partial purification of a fungal luciferin (7); and the investigation of the light emission of crude extracts that apparently required DPNH (8,9). None of these reports dealt with the process and mechanism of light emission beyond speculation.…”
Section: Ntro D U Ctlo Nmentioning
confidence: 99%